Cross‐border insolvency law in Hong Kong: Recognition of foreign schemes of arrangement. (27th July 2021) - Godwin, Andrew; Qu, Charles Zhen
Abstract: Hong Kong has no statutory cross‐border insolvency regime. Hong Kong courts have to resort to common law principles in circumstances where they are requested to recognise foreign insolvency proceedings and grant assistance. The nature and scope of these principles have been the subject of extensive debate in common law jurisdictions. In Re CW Advanced Technologies Ltd [2018] HKCFI 1705, Harris J identified the uncertainties associated with the common law position in Hong Kong. These uncertainties include whether a Hong Kong court may recognise a Singapore moratorium granted to facilitate a scheme of arrangement and, if so, whether the court may grant recognition where Singapore (i.e., the foreign jurisdiction) is not the country of incorporation. Harris J also noted the 'urgent need to enact a statutory cross‐border insolvency regime'. This article examines the scope of the common law powers in Hong Kong and seeks to clarify the possibility for members within a corporate group located outside Singapore, where the holding company has its centre of main interests in Singapore or is otherwise eligible to use the Singapore scheme regime, to obtain recognition and assistance in Hong Kong.